Komunikasi Akomodasi Antara Karyawan Lokal Dengan Karyawan Asing Di PT Sepco III Bengkulu - Soraya Yulita; Alfarabi (STAI Bumi Silampari, 2026)
This study aims to analyze accommodation communication between local and foreign employees at PT Sepco III Bengkulu in a multicultural work context. The study uses a qualitative approach with a post positivism paradigm. The analysis is based on Howard Giles' Communication Accommodation Theory (CAT), which includes convergence, divergence, maintenance, and over-accommodation strategies. Data was collected through interviews, observation, and documentation. The results of the study show that convergence strategies are the dominant pattern, especially carried out by local employees through adjustments in language, communication style, and work rhythm. Conversely, foreign employees tend to maintain a direct and assertive communication style as a form of maintenance, while divergence and over-accommodation arise situational. The interaction pattern that has been formed is asymmetrical, influenced by the local cultural orientation that emphasizes harmony and the hierarchy of foreign companies that employ local employees. Accomodation communication is not going smoothly, which could potentially lead to latent conflicts that may at any time escalate into open conflict.